Safety profile of immunosuppressants: Our experience - Ćulafić, Milica (Archives of Pharmacy, 2022)
Pharmacotherapy after liver transplantation include a combination of immunosuppressants to prevent graft rejection (calcineurin inhibitor, antimetabolite and corticosteroid) and antibacterial, antifungal and antiviral prophylaxis. In addition to potential preexisting comorbidities, metabolic complications/chronic conditions occur as a result of long-term immunosuppression. Given the complexity of post-transplant therapy and the pharmacokinetics of drugs, interactions are expected. The study aimed to detect the safety profile of immunosuppressants, including the assessment of drug-drug interactions. The study involved patients monitored at the Clinic of Gastroenterology and Hepatology, Clinical Center of Serbia, after liver transplantation, from November 2015 to November 2019. Medical records and laboratory reports were reviewed in the period of three months after transplantation. Adverse drug reactions (ADRs) have been reported. Interactions were analyzed using two databases: Lexicomp and Epocrates. We included 54 patients aged 44.7 ± 12.3, and recorded 252 follow-ups/hospitalizations. The average number of drugs per patient was 7. We noted following ADRs: Tacrolimus - hypomagnesemia (90.3%), infections (22.2%), nephrotoxicity (18.7%); mycophenolate mofetil - leukopenia 20.2%, increase in lactate dehydrogenase 11.1%, diarrhea 5.4%; everolimus - hypercholesterolaemia 25.0%, hypertriglyceridemia 12.3%. Potential drug-drug interactions in Lexicomp (225 D; 12 X) and Epocrates (543 monitor/modify; 139 avoid) were identified. Recognition, management and prevention of ADRs including timely resolution of drug-drug interactions is essential in improving long-term outcomes after liver transplantation. Frequent therapeutic drug monitoring, identification of clinical signs and parameters, and therapy optimization for each individual patient is a necessity. Hence, clinical transplant pharmacists have a vital role in multidisciplinary transplant team (1).